(3GdCNdGbs - (3eMeO CHh GdSYhO Hf YHO GdQMje GdYdhj GdTYQGfjs
(3ChdgG (B:s
(3agPG cJGH fajS UZjQ GdMLe YXje GdbOQ LeYJ LedI UGdMI ef CNdGb SjOfG hehdGfG GdTjN EHQGgje GdeJHhdi GdeMeOi s
(3BNQgG (B:s
(3hde jcf YfOge QGFMI eMHI ddg fSCdg Gddg GdYGajI abO HGf dc s
(3bWYI efgs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG RNGQa s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdJUha hGdBOGH GdTQYjIs